Interpersonal Difficulties Arising from Child Sexual Abuse: Differences Between Intra-familial and Extra-familial Abuse Victims - García-Montoliu, Carlos (Journal of interpersonal violence, 2025)
Child sexual abuse (CSA) often has serious implications for the victims. The scientific literature reflects a diversity of sequelae that may appear in the short and long term. Interpersonal difficulties have been shown to be one of the most common consequences. However, studies comparing these sequelae between victims of intra-familial (IF) and extra-familial (EF) CSA are scarce. The aim of this research was to analyze differences in dyadic satisfaction, sexual satisfaction, and attachment patterns in adulthood between Spanish IF victims, EF victims, and non-victims of CSA. The Sexual Victimization Subscale of the Juvenile Victimization Questionnaire, the Relationship Assessment Scale, the New Sexual Satisfaction Scale, and the Adult Attachment Questionnaire were administered to 140 adults (94 CSA victims and 46 non-victims) aged 18 to 54 years. CSA victims scored lower than the non-victims on the personal sexual satisfaction factor and attachment factors characterized by the need for approval, hostile resolution of conflicts, and emotional self-sufficiency. Statistically significant differences were also found between the victim groups in the factors characterized by the need for approval and communication of feelings and comfort with relationships showing the IF group to have more impairment in these areas than the EF group. In conclusion, CSA may have serious implications for the development of victims’ interpersonal relationships. The context of sexual abuse and the relationship between victim and offender appears to play a role in the development of relational problems. These findings highlight the need to implement specific strategies in the psychological treatment of victims depending on their relationship with the offender and the environment in which the abuse occurred.